A virus that has gone viral: amino acid mutation in S protein of Indian isolate of Coronavirus COVID-19 might impact receptor binding, and thus, infectivity. Issue 5 (15th May 2020) - Saha, Priyanka; Banerjee, Arup Kumar; Tripathi, Prem Prakash; Srivastava, Amit Kumar; Ray, Upasana
Abstract: Since 2002, β coronaviruses (CoVs) have caused three zoonotic outbreaks, SARS-CoV in 2002, MERS-CoV in 2012, and the recent outbreak of SARS-CoV-2 late in 2019 (also named as COVID-19 or novel coronavirus 2019 or nCoV2019). Spike (S) protein, one of the structural proteins of this virus plays key role in receptor (ACE2) binding and thus virus entry. Thus, this protein has attracted scientists for detailed study and therapeutic targeting. As the nCoV2019 takes its course throughout the world, more and more sequence analyses are being done and genome sequences are being deposited in various databases. From India, two clinical isolates have been sequenced and the full genome has been deposited in GenBank. We have performed sequence analyses of the Spike protein of the Indian isolates and compared with that of the Wuhan, China (where the outbreak was first reported). While all the sequences of Wuhan isolates are identical, we found point mutations in the Indian isolates. Out of the two isolates, one was found to harbor a mutation in its receptor-binding domain (RBD) at position 407. At this site, arginine (a positively charged amino acid) was replaced by isoleucine (a hydrophobic amino acid that is also a C-β branched amino acid). This mutation has been seen to change the secondary structure of the protein at that region and this can potentially alter receptor binding of the virus. Although this finding needs further validation and more sequencing, the information might be useful in rational drug designing and vaccine engineering.